The dynamic nature of exocytosis from large secretory vesicles. A view from electrochemistry and imaging. (March 2023) - Borges, Ricardo; Gu, Chaoyi; Machado, José-David; Ewing, Andrew G.
Highlights: Exocytosis dynamics are slower than by diffusion alone. Partial release appears to be dominant in dense core and some small vesicles. Partial release observed by both electrochemical and imaging methods. The fraction of exocytotic release is altered by drugs/ions. The fraction of exocytotic release with repeated stimulations reveals plasticity. Abstract: In this brief review, we discuss the factors that modulate the quantum size and the kinetics of exocytosis. We also discuss the determinants which motivate the type of exocytosis from the so-called kiss-and-run to full fusion and along the intermediate mode of partial release. Kiss-and-run release comprises the transient opening of a nanometer (approx. 2 nm diameter) fusion pore between vesicle and plasma membrane allowing a small amount of release. Partial release comprises a larger more extended opening of the pore to allow a larger fraction of released vesicle content and is what is observed as normal full release in most electrochemical measurements. Partial release appears to be dominant in dense core vesicles and perhaps synaptic vesicles. The concept of partial release leads to the fraction released as a plastic component of exocytosis. Partial vesicular distension and the kinetics of exocytosis can be modulated by second messengers, physiological modulators, and drugs. This concept adds a novel point of regulation for the exocytotic process. Graphical abstract: Image, graphical abstract